2019
DOI: 10.1016/j.ijom.2018.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Long-term quality of life outcomes of maxillomandibular advancement osteotomy in patients with obstructive sleep apnoea syndrome

Abstract: We evaluated the long-term impact of maxillomandibular advancement (MMA) surgery on the apneahypopnea index (AHI) and quality of life (QoL) in patients with obstructive sleep apnea syndrome (OSAS). The medical files of 12 OSAS patients undergoing MMA by one surgeon between 1995 and 1999 were retrospectively reviewed. Patients received a clinical assessment, polysomnography and QoL questionnaires as part of routine care preoperatively (n=12), within two year postoperatively (n=12), and again in 2016 (n=9). Succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Regarding the instruments, five articles used a single questionnaire [ 27 , 29 , 30 , 36 , 37 ], while eleven employed multiple questionnaires, with the most extensive one using six [ 38 ]. The most commonly referred instruments were the Epworth Sleepiness Scale (nine studies) [ 27 , 28 , 31 , 34 , 35 , 37 , 38 , 39 , 40 , 41 ], SF-36 (four studies) [ 32 , 38 , 39 , 42 ], Functional Outcomes of Sleep (three studies) [ 31 , 39 , 41 ], Ottawa Sleep Apnea (two studies) [ 36 , 39 ], and Rustemever’s method (two studies) [ 32 , 33 ]. The most evaluated outcomes were sleep quality, daytime function, facial aesthetics, dental function and emotional health.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the instruments, five articles used a single questionnaire [ 27 , 29 , 30 , 36 , 37 ], while eleven employed multiple questionnaires, with the most extensive one using six [ 38 ]. The most commonly referred instruments were the Epworth Sleepiness Scale (nine studies) [ 27 , 28 , 31 , 34 , 35 , 37 , 38 , 39 , 40 , 41 ], SF-36 (four studies) [ 32 , 38 , 39 , 42 ], Functional Outcomes of Sleep (three studies) [ 31 , 39 , 41 ], Ottawa Sleep Apnea (two studies) [ 36 , 39 ], and Rustemever’s method (two studies) [ 32 , 33 ]. The most evaluated outcomes were sleep quality, daytime function, facial aesthetics, dental function and emotional health.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of one cohort by Vigneron et al, the AHI increased to 25.5 at approximately 13 years after MMA, which would qualify as surgical failure by typical definitions [ 57 , 58 ]. In a cohort of 9 patients from an initial cohort of 12 followed for a median of 19 years, successfully treated patients showed no significant symptoms of sleepiness or change in quality of life measures covering headaches, concentration, insomnia, or snoring despite two patients relapsing to prior to procedure AHI values [ 59 ].…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Several studies have demonstrated its effectiveness, safety, and success in reducing daytime sleepiness and AHI in the short and long term 2,6,9–14. However, few studies have addressed the impact of MMA on the health-related quality of life (HRQOL) of patients with OSA 6,13–16…”
mentioning
confidence: 99%
“…2,6,[9][10][11][12][13][14] However, few studies have addressed the impact of MMA on the health-related quality of life (HRQOL) of patients with OSA. 6,[13][14][15][16] The assessment of HRQOL through patient-reported outcome measures has recently contributed to improving care strategies. This method considers the perception of the physical and psychosocial well-being of people who experience problems in their daily lives arising from health interventions.…”
mentioning
confidence: 99%